Hierarchical Design of Cross‐Linked NiCo2S4 Nanowires Bridged NiCo‐Hydrocarbonate Polyhedrons for High‐Performance Asymmetric Supercapacitor. (20th November 2022) - Zhao, Junping; Wang, Yahui; Qian, Yudan; Jin, Huile; Tang, Xinyue; Huang, Zaimei; Lou, Jiayi; Zhang, Qingcheng; Lei, Yong; Wang, Shun
Abstract: Engineering core‐shell materials with rationally designed architectures and components is an effective strategy to fulfill the high‐performance requirements of supercapacitors. Herein, hierarchical candied‐haws‐like NiCo2 S4 @NiCo(HCO3 )2 core‐shell heterostructure (NiCo2 S4 @HCs) is designed with NiCo(HCO3 )2 polyhedrons being tightly strung by cross‐linked NiCo2 S4 nanowires. This rational design not only creates more electroactive sites but also suppresses the volume expansion during the charge–discharge processes. Meanwhile, density functional theory calculations ascertain that the formation of NiCo2 S4 @HCs heterostructure simultaneously facilitates OH − adsorption/desorption and accelerates electron transfer within the electrode, boosting fast and efficient redox reactions. Ex situ X‐ray diffraction and Raman measurements reveal that gradual phase transformations from NiCo(HCO3 )2 to NiCo(OH)2 CO3 and then to highly‐active NiCoOOH take place during the cycles. Therefore, NiCo2 S4 @HCs demonstrates an ultrahigh capacitance of 3178.2 F g −1 at 1 A g −1 and a remarkable rate capability of 2179.3 F g −1 at 30 A g −1 . In addition, the asymmetric supercapacitor NiCo2 S4 @HCs//AC exhibits a high energy density of 69.6 W h kg −1 at the power density of 847 W kg −1 and excellent cycling stability with 90.2% retained capacitance after 10 000 cycles. Therefore, this novel structural design has effectively manipulated the interface charge states and guaranteed the structural integrity of electrode materials to achieve superior electrochemical performances. Abstract : Hierarchical candied‐haws‐like NiCo2 S4 @NiCo(HCO3 )2 core–shell heterostructure (NiCo2 S4 @HCs) is designed with NiCo(HCO3 )2 polyhedrons being tightly strung by cross‐linked NiCo2 S4 nanowires, which demonstrates an ultrahigh capacitance of 3178.2 F g ‐1 at 1 A g ‐1 and a remarkable rate capability of 2179.3 F g ‐1 at 30 A g ‐1, and a high energy density of 69.6 W h kg ‐1 in asymmetric supercapacitor device.